(untitled) ("Conference on Universal Science Research 2023", 2023)
This article is all about syllables and will give a definition for syllable definition, cover the types of syllables in English, and provide some syllable examples. We’ll also cover syllable division in other words, how to divide a word into its constituent syllables. We learned in the last unit that a syllable is a sonority peak encircled by less sonorous sounds. Since we now know how speech is formed, we can also conclude that the sounds produced with the vocal tract unobstructed are the most sonorous and have the highest acoustic energy. Sonority is defined as acoustic energy. Vowels are the most sonorous sounds. Conversely, consonants are less sonorous due to an obstruction in the vocal tract. Therefore, a syllable can alternatively be thought of as a vowel surrounded by a few consonants. That’s a fair starting definition, but as we’ll see in this unit and the next, it’s a little more complicated than that.